2020
DOI: 10.1111/psyp.13727
|View full text |Cite
|
Sign up to set email alerts
|

The N400 indexes acquisition of novel emotion concepts via conceptual combination

Abstract: The ability to learn new emotion concepts is adaptive and socially valuable as it communicates culturally held understandings about values, goals, and experiences. Yet, little work has examined the underlying mechanisms that allow for new emotion concepts and words to be integrated into the conceptual system. One such mechanism may be conceptual combination, or the ability to form novel concepts by dynamically combining previously acquired conceptual knowledge. In this study, we used event‐related potentials (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…For example, participants may have been able to construct instances of kreng jai by combining previous experiences of gratitude and guilt. Conceptual combination has been hypothesized to support performance in crosscultural emotion perception tasks (Hoemann, Crittenden, et al, 2019) and has been shown to underlie acquisition of novel emotion concepts (Hoemann et al, 2021). As such, it may represent an alternate mechanism of category learning: instead of creating emotion categories from scratch, participants may have productively applied existing category knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…For example, participants may have been able to construct instances of kreng jai by combining previous experiences of gratitude and guilt. Conceptual combination has been hypothesized to support performance in crosscultural emotion perception tasks (Hoemann, Crittenden, et al, 2019) and has been shown to underlie acquisition of novel emotion concepts (Hoemann et al, 2021). As such, it may represent an alternate mechanism of category learning: instead of creating emotion categories from scratch, participants may have productively applied existing category knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…However, Bridger et al and Strozak et al separated semantic priming test and semantic recognition test and found that FN400 was also associated with semantic information familiarity as well as the recognition process ( 41 , 42 ). However, in Hoemann et al's study exploring the acquisition of emotional concepts, the FN400 was considered to have similar functions to the N400 that reflect the processing of emotional meaning ( 21 ). The functional differences between N400 and FN400 in semantic research are still debated by researchers.…”
Section: Methodsmentioning
confidence: 99%
“…Because inconsistent scene pictures from the visual channel and inconsistencies in face and identity information could also evoke a more negative N400 component (18,19), researchers have found that the N400 may be an index for the processing of meaningful stimuli as well as information integration (20). Compared with emotional consistency, the sequential presentation of stimuli with conflicting emotional meanings elicited more negative N400 amplitudes, regardless of whether the target stimuli were faces (13,16) or words (21).…”
Section: Introductionmentioning
confidence: 99%